Influence Profitability, Policy debt, Policy Dividend, Investment Decision, And Firm Size to Company Value Manufacture Sub Sector Food And Drink Which Registered In the Indonesian Stock Exchange - Yoppy, Irene; Hartono, Ivany Artamevia; Hutahaean, Thomas Firdaus; Pandiangan, Saut Maruli Tua (Lembaga Riset Ilmiah, 2023)
The purpose of this report is to analyze and evaluate the effects of profitability, debt policy, and dividend policy. Investment Decision, and Firm Size, on the Company Value of Food and Beverage Sub Sector Manufacturing, which is listed on the Indonesia Stock Exchange. The approach used in this study is the Quantitative Approach Method. The population used comes from various producers listed on the Indonesia Stock Exchange from 2017 - 2021. The total number of samples used in the study was 85, which is the number of samples used by 17 different businesses over the five study periods. The research model is a linear multiple-regression model